Influence of the Epoxy Resin Process Parameters on the Mechanical Properties of Produced Bidirectional [±45°] Carbon/Epoxy Woven Composites - Ramírez-Herrera, Claudia A. (Polymers (Basel), 2021)
This work focuses on investigating the curing process of an epoxy-based resin—Aerotuf 275-34(TM), designed for aerospace applications. To study the curing degree of Aerotuf 275-34(TM) under processing conditions, woven carbon fiber fabric (WCFF)/Aerotuf 275-34(TM) composite laminates were produced by compression molding using different processing temperatures (110, 135, 160, and 200 °C) during 15 and 30 min. Then, the mechanical behavior of the composite laminates was evaluated by tensile tests and correlated to the resin curing degree through Fourier-transform infrared spectroscopy (FTIR) analysis. The results show the occurrence of two independent reactions based on the consumption of epoxide groups and maleimide (MI) double bonds. In terms of epoxide groups, a conversion degree of 0.91 was obtained for the composite cured at 160 °C during 15 min, while the measured tensile properties of [±45°] WCFF/Aerotuf 275-34(TM) laminates confirmed that these epoxy resin curing processing conditions lead to an enhancement of the composite mechanical properties.